Effect of Melampsora larici-populina on growthand biomass yield of eight clones of Populus nigra - V. Benetka; K. Černý; P. Pilařová; K. Kozlíková (Journal of Forest Science, 2011)
This study evaluates the effect of the identified pathogenic races E1, E2 and E3 of the leaf rust Melampsora larici-populina on some growth traits and biomass yield in the species Populus nigra. A field trial was conducted with 8 clones of P. nigra using fungicide-sprayed and unsprayed treatments in 3 replications of 4 plants. In the course of three years the occurrence of the rust was evaluated on a six-point scale. The plant height and stem diameter were measured during the trial. In the last year the plants were harvested and the dry weight was determined. In the untreated plants a significant negative correlation was found between the intensity of rust occurrence and the values of stem diameter and dry matter yield (P < 0.05). A decline in dry matter yield caused by the rust was low (below 9%) or zero in a half of the clones while it ranged between 19% and 28% in the other half of clones. In some clones the yield decline was relatively low although the expression of rust symptoms was rather high which could be attributed to a tolerance to the given pathogen.